Sekolah Unggulan: Pendekatan Pengembangan Kapasitas Sekolah - Syukkur, Ahmad (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2021)
One of the major themes in educational effectiveness research is school capacity building. This study investigates the implementation of the International Standard School (SBI) policy in Indonesia which can be seen as an effort of school capacity building improvement in the particular country. Using the program coherence dimension from the capacity-building framework, a qualitative study was conducted in a secondary school located in a small city in West Java, Indonesia, that involved in the program. It is found that the interpretation of the SBI policy was changing, which established international standard classrooms is the salient aspect of the implementation of the policy. It is discovered that becoming an SBI school has positive consequences with regard to the acknowledgment of its quality by the central government, besides the school can collect extra funds from parents with an amount nearly ten times that received from the central government. Document analysis reveals the school's difficulties to reach international requirements with particular to master in English by its teachers.